ChemInform Abstract: Synthesis of Functionally Substituted Isoxazole and Isothiazole Derivatives. Issue 16 (22nd April 2014) - Potkin, V. I.; Petkevich, S. K.; Kletskov, A. V.; Dikusar, E. A.; Zubenko, Yu. S.; Zhukovskaya, N. A.; Kazbanov, V. V.; Pashkevich, S. G.
Abstract A variety of ester compounds containing two isoxazole moieties [cf.